Paratesticular Pleomorphic Rhabdomyosarcoma: A Report of Two Cases. (12th February 2013) - Boulma, Rami; Gargouri, Mohamed Mourad; Sallemi, Ahmed; Chlif, Mohamed; Fitouri, Zouhaier; Kallel, Yosri; Nouira, Yassine
Abstract : Pleomorphic rhabdomyosarcoma (RMS) is a rare tumor with an aggressive behavior, described mainly in adulthood. Herein we present two cases of paratesticular pleomorphic RMS in 71- and 16-year-old patients with metastases at initial diagnosis. Histological, immunohistochemical, and ultrastructural findings were essential to confirm diagnosis. Few months after radical orchiectomy, both patients died before or just after starting adjuvant chemotherapy.